The provision of higher- and lower-skilled immigrant labour to the Canadian economy - Garnett Picot; Tahsin Mehdi (Economic and Social Reports)
This study assesses the skill level and occupations of recent immigrants in Canada by examining immigrants who landed in 2018 or 2019 and their occupational outcomes in May 2021. More recent results from the March 2024 Labour Force Survey are provided in some cases. The share of recent immigrants in lower-skilled or labourer jobs (35%) was almost as high as the share working in higher-skilled occupations (40%) in May 2021. However, recent immigrants and immigrants overall were much less likely than Canadian-born individuals to be in middle-skilled technical or trades jobs such as construction. Recent immigrants were more likely than their Canadian-born counterparts to be employed in higher-skilled occupations such as engineering and computer and information systems professions but less likely than Canadian-born individuals to be in nursing professions, partly because of the time it may take to become professional nurses.